2022
DOI: 10.1007/s12144-022-02808-6
|View full text |Cite
|
Sign up to set email alerts
|

Developing and validating the Japanese version of the situational Awe cale (SAS-J)

Abstract: The experience of awe, an emotional response to vast stimuli overwhelming ones’ current mental structure, has often been measured using a questionnaire method. The purpose of the present study was to develop and validate the Japanese version of the Situational Awe Scale (SAS), which is a useful tool for measuring awe experiences from the perspective of the discriminability between positive- and threat-awe. The present study investigated the factor structure and validity of the Japanese version of the SAS (SAS-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Awe is an emotional response to perceptually and conceptually vast stimuli that transcend one's current frames of reference (Keltner & Haidt, 2003). It has been studied in various fields, such as psychology, economics, neuroscience, immunology, and public health (Guan et al, 2018;Ibanez et al, 2017;Monroy & Keltner, 2022;Piff et al, 2015;Sawada & Nomura, 2020;Stellar et al, 2015;Sun et al, 2021;Takano & Nomura, 2022b;van Elk et al, 2019). Previous studies have shown that awe is associated with subjective psychological phenomena, such as a sense of self and consciousness, which highlights the need for a standardized questionnaire to assess the various dimensions of awe experiences (Bai et al, 2017;Rudd et al, 2012;Takano & Nomura, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Awe is an emotional response to perceptually and conceptually vast stimuli that transcend one's current frames of reference (Keltner & Haidt, 2003). It has been studied in various fields, such as psychology, economics, neuroscience, immunology, and public health (Guan et al, 2018;Ibanez et al, 2017;Monroy & Keltner, 2022;Piff et al, 2015;Sawada & Nomura, 2020;Stellar et al, 2015;Sun et al, 2021;Takano & Nomura, 2022b;van Elk et al, 2019). Previous studies have shown that awe is associated with subjective psychological phenomena, such as a sense of self and consciousness, which highlights the need for a standardized questionnaire to assess the various dimensions of awe experiences (Bai et al, 2017;Rudd et al, 2012;Takano & Nomura, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Universal components and cultural variations of awerelated phenomena have been identified via this scale. However, despite the creation and development of other scales to measure awe in Japan, the AWE-S has not yet been translated into the Japanese language (Nakayama et al, 2020;Sawada & Nomura, 2023). To facilitate further comprehensive cross-cultural comparisons, development of a Japanese version of the AWE-S, which can provide a deeper understanding of awe, is necessary.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Universal components and cultural variations of awe-related phenomena have been identified via this scale. However, despite the creation and development of other scales to measure awe in Japan, the AWE-S has not yet been translated into the Japanese language ( Nakayama et al , 2020 ; Sawada & Nomura, 2023 ). To facilitate further comprehensive cross-cultural comparisons, development of a Japanese version of the AWE-S, which can provide a deeper understanding of awe, is necessary.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies suggested that cultural similarities and differences in awe experiences were important perspectives to understand its generality and heterogeneity ( Bai et al , 2017 ; Nakayama et al , 2020 ; Nakayama & Uchida, 2020 ; Razavi et al , 2016 ; Sawada & Nomura, 2023 ). Specifically, it was necessary to consider how awe altered the sense of self and differed across cultures, although the small self-effect was a general and robust phenomenon ( Bai et al , 2017 ; Nomura et al , 2021 ; Takano & Nomura, 2021 ).…”
Section: Introductionmentioning
confidence: 99%